1997
DOI: 10.1023/a:1005841032371
|View full text |Cite
|
Sign up to set email alerts
|

Similarity between natural and recombinant human alpha-fetoprotein as inhibitors of estrogen-dependent breast cancer growth

Abstract: Alpha-fetoprotein (AFP) isolated from rodent amniotic fluid or human cord sera, upon incubation with a molar excess of estradiol, is converted to a form which inhibits estrogen-stimulated tissue growth. The purpose of this study was to determine whether recombinant human AFP produced in an E. coli expression system retained this function. The recombinant protein was similar to the natural protein isolated from pooled human cord sera in all functional aspects evaluated. It was detected by monoclonal and polyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…the peptide could be used after cancers have become tamoxifen-resistant (and when the patient has very few options), or b.) the peptide could be used in conjunction with tamoxifen, especially if we could show that lower doses of tamoxifen (or of both drugs) would be efficacious, thereby delaying onset of resistance to tamoxifen, or c.) the peptide could be used alone, in replacement of tamoxifen, especially since the pep tide, unlike tamoxifen, is not uterotrophic (18). Similar potential presumably exists for the prevention aspects of the drug vis a vis tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…the peptide could be used after cancers have become tamoxifen-resistant (and when the patient has very few options), or b.) the peptide could be used in conjunction with tamoxifen, especially if we could show that lower doses of tamoxifen (or of both drugs) would be efficacious, thereby delaying onset of resistance to tamoxifen, or c.) the peptide could be used alone, in replacement of tamoxifen, especially since the pep tide, unlike tamoxifen, is not uterotrophic (18). Similar potential presumably exists for the prevention aspects of the drug vis a vis tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…A bioassay for antiestrotrophic activity was performed by using an immature mouse uterine growth assay based on previous studies, which demonstrated that i.p. administration of 0.5 jxg E 2 to these mice doubled their uterine weights with a corresponding increase in mitotic figures by 24 h after E 2 (3,18). Swiss/Webster female mice, 6-8 g in body weight (13-15 days old), were obtained from Taconic Farms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transgenic mice strain MMTV-neu (ErbB-2) with transplanted breast cancer showed that the liver of tumor-bearing mice displayed a fetal phenotype with expression of α-fetoprotein (AFP) (8). AFP acts as a growth factor and biological response modifier, which affects cell proliferation (9)(10)(11)(12). AFP functions as a transporter of various ligands, such as steroid hormones and hemoglobin degradation products (bilirubin) (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%